Motivasi Orang Tua Dan Guru Untuk Mengembangkan Literasi Dasar Anak - Pratiwi, Dwi Septia, Dr. Lisnawati Ruhaena, S.Psi., M.Psi, Psi (2017)
The development of literacy ability from pretending or imitating of reading-writing (emergent literacy) is influenced by the children's development of sustainable literacy, the concept of children's literacy, and efforts made by parents and teachers. The basic literacy or emergent literacy is the development of skill, knowledge and behavior which is the early development or underlying the reading and writing, and environment is as the support of the development. If the parents' and teachers' motivation has been correctly directed which is the motivation that give a basic literacy that has been suitable with the development stage of the children, it will give benefits to the children to be ready for reading and writing in a real situation, therefore, in future, the children will have a good reading achievement so they will be easy in understanding the content of the reading. The purposes of this research are to know and to understand how the parents' and the teachers' motivation develop the children's basic literacy. The research question is how the parents' and the teachers' motivation develop the children's basic literacy. Informants in this research are parents and teachers of children aged 4 - 5 years old and studied in kindergarten of grade A. The data collection was conducted through interview and observation. The method of data analysis in this research used a descriptive analysis. The results of the research revealed that the parents' and the teachers' motivation in developing the children's basic literacy had been underlie with the right understanding on the parents' and teachers' knowledge about the importance of the children's basic literacy and children are not forced to read and write fluently without a suitable process according to the children's age and activities of learning in a fun atmosphere. Children of 4-5 years old have been in the period of phonetic writing stage in which the children begin to connect the writing form and the phoneme and the take-off reading stage in which they begin to be excited in knowing alphabets, paying attention to the environment through alphabets reading everything around them. The reinforcement of behavior intensity was conducted through relaxing activities and providing the facilities of reading and writing. The activities were conducted according to the children's development stage through a fun atmosphere and indoor as well as outdoor situations. The parents and the teachers spent their time to accompany the children in conducting the learning of reading and writing.